Holistic retirement : the current state and perceptions of six dimensions of wellness and financial wellness of Singaporeans on retirement. - Hee, Yuen Bao. (2009)
Increasing life expectancy and falling birth rates have led to an ageing population in Singapore. This increase in retirement years have necessitated proper planning for retirement and having accurate views of retirement and retirement planning.